Penyuluhan Kesehatan Tentang Sanitasi Hygiene pada Masyarakat di Pulau Pramuka Kepulauan Seribu - Ariska Nurchotimah; Khusnul Khotijah; Kristina Finsensia Nole Waleng; Irfan Makshum Jauhari; Sentot Mulyanto; Jessica Rusli (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Sanitation and hygiene are crucial aspects of public health, especially in island areas like Pramuka Island, Kepulauan Seribu. This activity aims to enhance the community's understanding and awareness of hygiene sanitation through health education. The methods used include interactive education, health screening, and evaluation using pre-test and post-test questionnaires. The results of this activity showed a significant increase in participants' knowledge levels, from 50% before the education to 85% afterward. Health screening revealed a tendency for high cholesterol levels, as well as some cases of blood sugar and uric acid levels exceeding normal limits among the residents. Analysis of local snacks did not show any contamination with borax and formalin, indicating food safety awareness among vendors. Meanwhile, marine biota exploration found the potential of seagrass (Cymodocea serrulata) with alkaloid content that can be further developed. These findings highlight the importance of continuous education, targeted health interventions, and the utilization of local natural resources to improve the quality of life of Pramuka Island residents.